Graph MMU design for Zedwulf - Han, Jianglei (2014)
We previously assembled a miniature Beowulf cluster using 32 ZedBoards, the Zedwulf. Installed with Xillybus 1.3 OS on the Processing System, inter-nodal communication are possible